1959
DOI: 10.1115/1.4008118
|View full text |Cite
|
Sign up to set email alerts
|

A Boundary-Layer Treatment of Laminar-Film Condensation

Abstract: The problem of laminar-film condensation on a vertical plate is attacked using the mathematical techniques of boundary-layer theory. Starting with the boundary-layer (partial differential) equations, a similarity transformation is found which reduces them to ordinary differential equations. Energy-convection and fluid-acceleration terms are fully accounted for. Solutions are obtained for values of the parameter cpΔT/hfg between 0 and 2 for Prandtl numbers between 1 and 100. These solutions take their place in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
58
0
1

Year Published

1965
1965
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(64 citation statements)
references
References 0 publications
5
58
0
1
Order By: Relevance
“…Chen [9] considered the vapor to be stagnant far from the interface while considering it to be dragged downward by the falling film of the condensate near the interface. He found that the values of Nusselt numbers are smaller than these reported by Sparrow and Gregg [4] and agree better with experimental data.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Chen [9] considered the vapor to be stagnant far from the interface while considering it to be dragged downward by the falling film of the condensate near the interface. He found that the values of Nusselt numbers are smaller than these reported by Sparrow and Gregg [4] and agree better with experimental data.…”
Section: Introductionsupporting
confidence: 64%
“…Sparrow and Gregg [4] included momentum effects and energy convection in the Nusselt model [1]. They used the boundary layer theory in the mathematical modelling.…”
Section: Introductionmentioning
confidence: 99%
“…Following the pioneering analysis performed by Nusselt [3] on laminar free convection film-wise condensation, a number of studies were reported involving refinements to his assumptions concerning the effects of sub-cooling, the temperature profile in the condensate film, the effects of inertia and drag [4][5][6]. And his theory has been extended to condensation with the presence of a non-condensable gas [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…The case of condensation on the outside of a vertical circular cylinder was first investigated by Sparrow and Gregg [2]. There it was assumed that the thickness of the condensate layer was small compared with the radius of the cylinder and so the conventional boundary-layer approximation may be evoked.…”
Section: Introductionmentioning
confidence: 99%
“…Two modifications of the Sparrow and Gregg [2] condensate flow are manifest. The first is that far downstream of the thermal leading edge the condensate thickness may be of the same order as the radius of the cylinder and so the above assumption of Sparrow and Gregg is no longer valid.…”
Section: Introductionmentioning
confidence: 99%